Bio-Inspired Optimization of a Fuzzy System Inference for the Generation of Psychedelic Effects in Digital Images (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
The generation of effects on digital images through computers has created a new age for different artistic trends. Particularly, the digital age has had a remarkable impact on psychedelic art. In this paper we propose a fuzzy inference system for color manipulation in digital images with the purpose of modifying their artistic style. The proposed system aims to create a combination of different colors to generate a new visual sensation, much like the current psychedelic art. The proposed system is divided into two parts. The first part of the method consists in the creation of a fuzzy logic system that, through fuzzy sets, and rules of change generates color images that produced this psychedelic effect. In the second part, the differential evolution algorithm optimizes parameters of the proposed inference system and adjusts the results to the psychedelic art style used.
Keywords: Evolutionary art; colorimetry; fuzzy logic; fuzzy sets; image processing; optimization